Enhancing Financial Literacy for Indonesian Students in Egypt through Amānāh Finance Training - Latifah, Luluk Latifah; Saputra, Fathi Fathurrahman; Nasrullah, Dede; Huda, Fatkur (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
As the phenomenon of Indonesian students studying abroad increases, the number of concerns of Indonesian students in facing the challenges of financial management while studying abroad also increases. That is why proper and correct financial management is needed. Amānāh finance is financial management both individually and institutionally based on the values ​​of Amānāh in order to realize blessings. The purpose of the community service program is to socialize personal financial management while studying in Egypt. The target of this community service program is Indonesian students who are studying in Egypt. The method used is to conduct training or workshops on personal financial management based on the values ​​of Amānāh . The training begins with a pre-test before delivering the socialization material about Amānāh finance. The pre-test is to see the extent of the training participants' understanding of Amānāh financial management. The training ends with a post-test, to see the increase in understanding after being given socialization and training related to Amānāh finance. The results of community service show an increase in students' understanding of financial management material based on Amānāh values. This can be seen from the results of the pre-test and post-test of students who have increased. When the pre-test was carried out on the questions given, the correctness value obtained ranged from 70% - 80%, and after being given the material and a post-test was held, the value increased to 95% - 100%.